Public Financial Analysis in the Preparation of Indonesia State Budget (APBN) 2018 - Cucun Ahmad Syamsurijal (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
In Indonesia, the function of the budget is carried out by the government as a branch of executive power in charge of preparing the draft of State Budget and Revenue (R-APBN), together with the House of Representatives of the Republic of Indonesia (DPR-RI) as a branch of legislative power in charge of participating in discussing and approving the R-APBN, including oversight of the implementation of the State Budget and Revenue (APBN). During the initial observation process and the results of interviews conducted, the author found several indications of problems relating to the State Budget of the Republic of Indonesia in 2018, such as not all the components are on time so that a delay can affect the existing cycle and The attraction of interests that can not be avoided starting from the interests of groups as well as individual interests. Based on the results of research on the analysis of Public Finance in the preparation of the State Budget (APBN) of the Republic of Indonesia in 2018, it can be concluded The existence of a time delay in the realization of the discussion schedule for the Draft Bill on the 2018 APBN has affected the existing cycle.